2016
DOI: 10.1016/j.socscimed.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and HIV-positive women's non-adherence to antiretroviral medication for the purpose of prevention of mother-to-child transmission in Lusaka, Zambia

Abstract: Background Prevention of mother-to-child transmission (PMTCT) depends critically on HIV-positive women’s adherence to antiretroviral drugs during and after pregnancy. Adherence among pregnant and breastfeeding women remains a challenge across sub-Saharan Africa. Power dynamics within couples, such as intimate partner violence, has largely been neglected in research regarding PMTCT adherence. Objective This study aims to determine if there is a relationship between intimate partner violence and non-adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 44 publications
10
98
3
Order By: Relevance
“…Women LWHA reported that CD4 machines were not working most of the time and could take a long time to be fixed; as a result, they were unable to test their CD4 counts, a measure which is very important for patient monitoring. This observation is in accordance with a systematic review in Malaysia, which showed that a lack of CD4 testing and delays in receiving CD4 results were contributing factors to HIV-positive patients becoming lost to care in SSA (19, 20). …”
Section: Discussionsupporting
confidence: 91%
“…Women LWHA reported that CD4 machines were not working most of the time and could take a long time to be fixed; as a result, they were unable to test their CD4 counts, a measure which is very important for patient monitoring. This observation is in accordance with a systematic review in Malaysia, which showed that a lack of CD4 testing and delays in receiving CD4 results were contributing factors to HIV-positive patients becoming lost to care in SSA (19, 20). …”
Section: Discussionsupporting
confidence: 91%
“…Notably, there was a significant interaction between female-directed emotional IPV, women’s participation in household decisions, and male partner controlling behaviors—with emotional IPV driving the relationship with uptake of infant HIV testing. Our findings add to the growing body of literature linking different forms of IPV to poor medical outcomes across the continuum of care for HIV-infected mothers and their children [19, 3234]. Our findings also underscore the importance of examining IPV as a multidimensional phenomenon [35] and including emotional/psychological forms of abuse as potential predictors for poor health outcomes.…”
Section: Discussionsupporting
confidence: 58%
“…The original aim of the study was to explore the relationship between gender power dynamics and HIV-positive women’s adherence across the PMTCT cascade of care, including ART adherence during and after pregnancy [12], safe infant feeding [13], and pediatric HIV testing [14]. All of the participants from the parent study are included in our sub-analysis, which expands the previous work by exploring status disclosure to male partners as the outcome of interest.…”
Section: Methodsmentioning
confidence: 99%